Pleural amyloidosis mimicking malignant mesothelioma - Min Yeong Kim; Tae Jung Kim; Joungho Han; Bo Da Nam; Kyung Soo Lee (Precision and Future Medicine, 2017)
Pleural involvement of amyloidosis is rare and usually manifested as persistent massive effusion. However, it may present as pleural nodules or plaques without massive effusion. A 55-year-old man was referred for abnormalities of chest radiography and the computed tomography (CT) exam revealed multiple pleural nodules without effusion in the left hemithorax. The radiologic impression was pleural malignancy, and whole body 18F-fluorodeoxyglucose positron emission tomography-CT exam was performed. Not only corresponding pleural nodules but also other areas along the left pleura were hypermetabolic, whereas no hypermetabolic lesions were noted outside of the thorax. Preoperative diagnosis was made as malignant mesothelioma. During left pleuropneumonectomy, multiple hard whitish nodules or plaques were found along the pleura, and which were proven to amyloidosis on frozen section. The patient underwent not left pleuropneumonectomy but folup. Because of difficulty of accurate diagnosis, we report the localized pleural amyloidosis for awareness of the disease.